(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The research aims to know the concept of creative accounting and the practices used by the management in measuring and disclosing accounting information in the financial statements to achieve its objective. Also, aim to explore the extent to which these practices affect the qualitative characteristics of accounting information identified by the joint venture of FASB & IASB, by establishing the interrelationship between creative accounting practices with the qualitative characteristics and the combined effect of their variables and their branches. The researcher adopted in the theoretical framework and formulating the questions of the research problem and its hypotheses on the deductive approach by using the available resources from Arab and foreign sources of books and previous studies related to the subject of research. In the exploratory study, in order to test hypotheses, the researcher conducted a questionnaire for a sample of academics and professionals to determine the impact of these practices on the qualitative characteristics of the accounting information, and if these characteristics according to the joint venture contribute in one way or another to the reduction of creative accounting practices. The most important conclusion of this study is that the concepts of the qualitative characteristics of the accounting information developed by the FASB and the IASB have been achieved by reconciling the old characteristics of both chambers to improve the quality of accounting information, and to be more relevant to the substance of the information and its value to the decision-maker (Fundamental and Enhancing) not by its nature (primary and secondary). However, from the point of view of research sample respondents from academics and professionals, that the efforts of the joint venture to develop the concepts of qualitative characteristics of the accounting information did not limit the impact of creative accounting practices, where the results of the statistical analysis showed a statistically significant effect of the independent variable; the creative accounting practices in each of Fundamental characteristics; relevance and faithful representation as an dependent variables.